Teacher Perceptions of Self-Efficacy in Teaching Online During the COVID-19 Pandemic - John Rodari Meisner; Jennifer M. McKenzie (Athens Institute for Education and Research, 2023)
To examine the effects of the sudden shift to online instruction due to the COVID-19 pandemic in the early months of 2020, we sought to get a firsthand understanding of the experiences of teachers who were required to make the change to full online teaching. Teaching online requires technological knowledge, but it also requires a different pedagogy in order to keep students engaged and motivated to learn. Many educators indicated that this was a significant challenge. Our goal was to illuminate teachers' experiences in order to include their voices in changes to educator preparation programs. A total of 699 complete survey responses were received representing educators in several grade levels working in nine states in the United States. Qualitative analysis revealed that many responses were related to extant research on teachers' self-efficacy. Thus, this paper will shed light on the experiences of educators during the first semester of 2020 including the months of January through April, and teachers' perceived efficacy. We find that teachers felt more efficacious regarding aspects of online teaching over which they felt an internal locus of control, such as delivery of curriculum and their own skill in the use of technology. For items over which they had less control, such as parental support and involvement, student motivation, and student access to adequate technology, teachers indicated much less efficacy. The majority of responses paint a complicated and somewhat dismal picture of the loss of personal connection with their students. Based on these data, recommendations for both education preparation programs, and policy are discussed such as districts and schools must provide sufficient professional learning opportunities and create a culture of collaboration amongst teachers that can assist them in building internal school capacity for good online instruction for their students. The COVID-19 pandemic should be used as an opportunity to evaluate gaps in digital equity and make positive strides to ensure all students, regardless of race, disability, economic background, or geographic location, have full access to quality online education.